АRBOREAL HEMIPTERA (HEMIPTERA, HETEROPTERA) OF SOUTH-EASTERN KAZAKHSTAN (Experimental biology, 2024)
The article presents the results of studies of arboreal hemiptera in Southeastern Kazakhstan, conducted in 2023. As a result of the study, 37 species of arboreal hemiptera belonging to 8 families were identified. Of these, families were known: Miridae (8 species), Tingidae (7 species), Anthocoridae (6 species), Nabidae, Lygaeidae (4 species each), Acanthosomatidae, Pentatomidae (3 species each), Aradidae (2 species). According to their habitat, arboreal hemiptera of Southeastern Kazakhstan are divided into several groups: dendrobionts (24 species), dendro-tamnobionts (8 species), dendro-tamno-hortobionts (2 species), dendro-hortobionts (3 species). They are divided by food connections into zoophages (11 species), zoophytophages (4 species), phytophages (20 species) and mycetophages (2 species). According to the number of generations per year, all species of woody hemiptera of Southeastern Kazakhstan can be divided into several groups: 1) monovoltine (25 species), 2) bivoltine (7 species), 3) polyvoltine (3 species), 4) acyclic species (2 species). Different species of hemiptera have different requirements for the degree of moisture content of the habitat. On this basis, the following ecological groups of species can be distinguished: mesophiles (36 species), only Orsillus maculatus is a mesoxerophile. Hemiptera belong to insects with incomplete transformation and go through the following stages of development – egg, larva and imago. They are characterized by wintering at different stages of development. In most species, winter diapause occurs at the imago stage (28 species), at the egg stage (6 species), at the imago and larva stage (3 species). Arboreal hemiptera of Southeastern Kazakhstan are found in 13 zoogeographic regions: Neotropical-Holarctic (1 species), Holarctic (5 species), Trans-Palearctic (6 species), Trans-Palearctic-Ethiopian (1 species), West Palearctic (5 species), East Palearctic (3 species), Trans-Eurasian (8 species), West Eurasian (2 species), Orthatetic (1 species), Orthatetic-Tibetan (1 species), Turanian (1 species), Turano-Gobi (2 species), Iranian-Turanian (1 species).
Keywords: South-Eastern Kazakhstan, arboreal hemiptera, Heteroptera